Coupling of spectrin and polylysine to phospholipid monolayers studied by specular reflection of neutrons. - Johnson, S; Bayerl, T; Weihan, W; Noack, H; Penfold, J; Thomas, R; Kanellas, D; Rennie, A; Sackmann, E (1991)
The technique of specular reflection of neutrons is applied for the first time to study the charge-dependent interaction of the protein spectrin and the polypeptide poly-L-lysine with model phospholipid monolayers in the condensed phase state. We first established the structure of a pure monolayer of dimyristolyphosphatidylcholine (DMPC) in both the expanded and condensed fluid phase states without protein in the subphase. The thickness of the hydrocarbon chains increases from 11.4 +/- 1.5 A in the expanded state to 15.8 +/- 1.5 A in the condensed state, whereas the head group region is approximately 10 A thick for both phase states. When spectrin is present in the subphase, the dimensions of DMPC in the condensed state are not significantly affected, but there is approximately 0.09 volume fraction spectrin in the head group region. Lipid-spectrin coupling is enhanced by electrostatic interaction, as the volume fraction of spectrin in the head group region increases to 0.22 in a mixed monolayer of DMPC and negatively charged dimyristolyphosphatidylglycerol in the condensed state. In contrast to spectrin, polylysine does not penetrate the head group region, but forms a layer electrostatically adsorbed to the charged head groups.